Evaluation of Antemortem Diagnostic Techniques in Goats Naturally Infected With Scrapie - Mammadova, Najiba; West Greenlee, M. Heather; Moore, S. Jo; Hwang, Soyoun; Lehmkuhl, Aaron D.; Nicholson, Eric M.; Greenlee, Justin J. (Frontiers in Veterinary Science, 2020)
Scrapie is a naturally occurring transmissible spongiform encephalopathy (TSE) that affects sheep and goats. Sheep and goats can be infected with scrapie as lambs or kids via contact with the placenta or placental fluids, or from ingestion of prions shed in the environment and/or bodily fluids (e.g., saliva, urine, and feces). Like other TSEs, scrapie is generally not diagnosed before extensive and irreversible brain damage has occurred. Therefore, a reliable method to screen animals may facilitate diagnosis. Additionally, while natural scrapie in sheep has been widely described, naturally acquired goat scrapie is less well characterized. The purpose of this study was to better understand natural goat scrapie in regard to disease phenotype (i.e., incubation period, clinical signs, neuroanatomical deposition patterns of PrPSc, and molecular profile as detected by western blot); and to evaluate the efficacy of antemortem tests to detect scrapie positive animals in a herd of goats. Briefly, 28 scrapie-exposed goats were removed from a farm depopulated due to previous diagnoses of scrapie on the premises and observed daily for 30 months. Over the course of the observation period, antemortem biopsies of recto-anal mucosa-associated lymphoid tissue (RAMALT) were taken and tested using immunohistochemistry and real-time quaking induced conversion (RT-QuIC), and retinal thickness was measured in vivo using optical coherence tomography (OCT). Following the observation period, immunohistochemistry and western blot were performed to assess neuroanatomical deposition patterns of PrPSc and molecular profile. Our results demonstrate that antemortem rectal biopsy was 77% effective in identifying goats naturally infected with scrapie, and that a positive antemortem rectal biopsy was associated with the presence of clinical signs of neurologic disease and a positive dam status. We report that changes in retinal thickness are not detectable over the course of the observation period in goats naturally infected with scrapie. Finally, our results indicate that the accumulation of PrPSc in central nervous system (CNS) and non-CNS tissues is consistent with previous reports of scrapie in sheep and goats.